Effects of scanning speed on mechanical, wear property, and corrosion behavior of CP-Ti fabricated by the selective laser melting technique - Chen, Weimin; Hu, Jinlong; Wen, Zhuhao; Lin, Haoqin; Sun, Liying; Zhang, Qiang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2026)
In this study, CP-Ti was prepared using the selective laser melting (SLM) technique to systematically investigate the effect of scanning speed on microstructure, mechanical properties, wear properties, and corrosion behavior. The optimum relative density of 99.87±0.12% was achieved at a scanning speed of 800 mm/s, with corresponding tensile strength, yield strength, elongation, and hardness values of 543±17 MPa, 453±7 MPa, 14±1%, and 294±4 HV, respectively. Additionally, SLM-processed CP-Ti with optimum relative density exhibited the lowest wear rate (2.72×10-7 mm2/N) and excellent corrosion resistance. These results indicate that CP-Ti with high relative density, strength, and hardness, low wear rate, and excellent corrosion resistance can be fabricated by controlling the scanning speed, making it well-suited for biomedical implant applications.
Keywords: Selective laser melting (SLM); CP-Ti; Scanning speed; Mechanical and wear properties; Corrosion behavior